Weight and height growth of malnourished school-age children during re-feeding. Three historic studies published shortly after World War I. Issue 12 (December 2018) - Hermanussen, M.; Bilogub, M.; Lindl, A.; Harper, D.; Mansukoski, L.; Scheffler, C.
Abstract Background In view of the ongoing debate on "chronic malnutrition" and the concept of "stunting" as "a better measure than underweight of the cumulative effects of undernutrition and infection (WHO)", we translate, briefly comment and re-publish three seminal historic papers on catch-up growth following re-feeding after severe food restriction of German children during and after World War I. The observations were published in 1920 and 1922, and appear to be of particular interest to the modern nutritionist. Results The papers of Abderhalden (1920) and Bloch (1920) describe German children of all social strata who were born shortly before World War I, and raised in apparently "normal" families. After severe long-standing undernutrition, they participated in an international charity program. They experienced exceptional catch-up growth in height of 3–5 cm within 6–8 weeks. Goldstein (1922) observed 512 orphans and children from underprivileged families. Goldstein described very different growth patterns. These children were much shorter (mean height between −2.0 and −2.8 SDS, modern WHO reference). They mostly failed to catch-up in height, but tended to excessively increase in weight particularly during adolescence. Conclusion Whereas Abderhalden and Bloch illustrate rapid height catch-up in children from intact social background, Goldstein's observations in orphans and children from poor social background parallel the growth patterns observed in children of modern middle and low-income countries. The historic observations question the current concept of stunting as prima facie evidence of malnutrition and chronic infection, and support the view that "the child's longitudinal growth is largely independent of the extent and nature of the diet".